A case series of scrub meningoencephalitis from a tertiary care center in North India - Vikas Suri; Harpreet Singh; Kunwer A Ary; Manisha Biswal; Chirag K Ahuja; Parampreet Kharbanda; Navneet Sharma (Annals of Indian Academy of Neurology, 2023)
Scrub typhus infection is reemerging leading cause of acute febrile illnesses in post-rainy or monsoon season in Southeast Asia. It is caused by Orientia tsutsugamushi and spread by the bite of chiggers, larval forms of trombiculid mites. The clinical picture can range from simple acute febrile illness to multiorgan dysfunction. Neurological manifestations also vary from aseptic meningitis, meningoencephalitis, cerebral infarction, acute disseminated encephalomyelitis, transverse myelitis, and psychiatric manifestations. Here, we present a case series of eight cases of scrub meningoencephalitis diagnosed based on clinical, laboratory, and radiological criteria.